Improving the Financial Mechanisms for the Investment Activities of Insurance Companies in the CIS Countries (Commonwealth of Independent States) - qizi, Gulirano Nosirova Abdulaziz (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Investment activity allows the insurance company to use part of the investment income received to compensate for the negative financial result of direct insurance operations in the event of an increase in losses, even in the event of an uneven distribution of risk or the occurrence of catastrophic risks. In such a situation, the assessment of investment potential should be given in terms of the ratio of insurance payments and premiums. The issues of improving the financial mechanisms for the investment activities of insurance companies in the CIS countries have not been fully studied in research and theoretical studies conducted within the framework of this topic. This provision determines the level of relevance of the studied scientific and practical problems and proposals and recommendations for their elimination.